2008
DOI: 10.1007/s12072-008-9088-8
|View full text |Cite
|
Sign up to set email alerts
|

Virologic, serologic, and biochemical outcomes through 2 years of treatment with entecavir and lamivudine in nucleoside-naïve Chinese patients with chronic hepatitis B: a randomized, multicenter study

Abstract: Purpose Entecavir demonstrated superior virologic and biochemical benefits over lamivudine at 48 weeks in nucleoside-naïve Chinese patients with chronic hepatitis B (CHB). We evaluated the effect of continued entecavir and lamivudine treatment in patients who continued treatment in year 2 and the off-treatment durability of patients who achieved a protocol-defined consolidated response at week 48. Methods Chinese adults (n = 519) with CHB were randomized to a minimum of 52 weeks of treatment with entecavir 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Safety findings for the first 2 years of the study have been published elsewhere [10,11]. In general, the safety of entecavir was comparable with that of lamivudine.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Safety findings for the first 2 years of the study have been published elsewhere [10,11]. In general, the safety of entecavir was comparable with that of lamivudine.…”
Section: Resultsmentioning
confidence: 76%
“…Chronic hepatitis B is highly prevalent in China. The results of entecavir trials performed in China are encouraging as they have demonstrated superior efficacy of entecavir compared with lamivudine in Chinese patients, with comparable safety and tolerability [8,10,11]. Persistently elevated HBV DNA levels increase the risk of development of cirrhosis and hepatocellular carcinoma in persons with CHB [14], and this relationship remains consistent when both baseline and follow‐up HBV DNA and ALT values are taken into consideration [15].…”
Section: Discussionmentioning
confidence: 99%
“…While, high rates of resistance in nucleoside-naïve patients during 5 years of lamivudine therapy, rates of phenotypic resistance were 17, 40, 57, 67 and 69% respectively Keeffe et al, 2006). These findings supported the selection of entecavir as a primary therapy that enabled prolonged treatment with potent viral suppression and minimal resistance, but we could not conduct this metaanalysis because the studies of comparing the efficacy of entecavir and lamivudine for chronic hepatitis B treatment which exceeded 96 weeks were rare (Gish et al, 2007;Yao et al, 2008;Chang et al, 2008).…”
Section: Discussionmentioning
confidence: 86%
“…However, in an earlier study comparing entecavir and lamivudine, entecavir demonstrated similar virologic, biochemical, and serologic outcomes in nucleos(t)ide-naïve Chinese patients with CHB 24. Although a higher proportion of patients treated with entecavir achieved HBV DNA <300 copies/mL (79% versus 46%; P <0.0001), similar proportions of entecavir-treated and lamivudine-treated patients achieved confirmed ALT normalization and HBeAg seroconversion, and the safety profile was similar between the groups.…”
Section: Entecavir Versus Lamivudinementioning
confidence: 91%